Islamic Legal Traditionalism in the Consideration of Polygamous Validation (Analysis of Decisions on the Granting the Validation of Unregistered Marriage in Polygamy Cases After the Enactment of SEMA No. 3/2018) - Herlina, Nina; Falah, Mohammad Bachrul; Hermawati, Kiki Ayu (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2024)
After the enactment of SEMA No. 3/2018, the issue of unregistered polygamous validation has become a new polemic in religious courts. Decision No. 130/Pdt.G/2020/Ms.Bna and No. 311/Pdr.P/2022/PA.Bjb granted the application for unregistered polygamous validation, thus raising a question, what kind of legal considerations underlie the judges to oppose SEMA No. 3/2018? This study examines the consideration of granting the validation of unregistered polygamy by judges in the two decisions above to find out the typology of Islamic legal thinking in them. This research is a normative legal research with a case approach. The results showed that the judges used the legal doctrine of previous scholars as the basis for granting the application for the validation of unregistered polygamy, thus reflecting a traditional style of thinking. This thinking is evident when: 1) The judge based the validation of the applicant's second marriage only on the validity of the unregistered marriage; 2) The judge did not consider the conditions for the permissibility of polygamy due to emergency conditions; and 3) The judge also did not explore the potential power relations in the polygamy permit from the first wife which allowed for coercion. This research shows that the traditionalism of Islamic legal thought is used by judges to counter the policy of the Supreme Court Circular that has taken effect.